Reseña de Jesús Girón, Ricardo Lázaro, Fernando Ramón (eds.), “Me amó y se entregó por mí” (Gal 2,20). Libro homenaje a Juan Miguel Díaz Rodelas, Maliaño (Cantabria) - Taranzano, Adrián (Revista Bíblica, 2025)
Jesús Girón, Ricardo Lázaro, Fernando Ramón (eds.), “Me amó y se entregó por mí” (Gal 2,20). Libro homenaje a Juan Miguel Díaz Rodelas, Maliaño (Cantabria): (Presencia Teológica, 313), Sal Terrae 2023, X + 872 pp. ISBN 978-84-293-3175-2.